2020
DOI: 10.1515/ohs-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Growth parameters of invasive gibel carpCarassius gibelio(Bloch, 1782) in Lake Marmara (Turkey)

Abstract: The objective of this study was to determine growth parameters, such as age–length and length–weight relationships, as well as condition factors and sex ratio, of the Carassius gibelio (Bloch, 1782) population in Lake Marmara (western region of Turkey), which is one of the most important fishing areas. Fish were caught on a monthly basis by gillnets and trammel nets (mesh size 10–50 mm) between March 2012 and February 2013. A total of 1058 specimens (809 females and 249 males) were examined. The female–male ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…On the contrary, the a value in different studies conducted in the same lakes was higher than the current study [19,27,29,33,37,42,44,45,47,48,57,58] . The b value calculated in this study higher than the b value of C. Gibelo studied in Danube River, Bafra Dam, İkizcetepeler Dam, Gelingüllü Dam, Seyitler Dam, Büyük Menderes basin, Beyşehir and Marmara Lake [52,51,58,48,27,47,44,45,57,33] . The length-weight relationship parameters can be affected by factors such as sampling period, nutritional status, heightweight distribution, reproductive period, age, and gonad maturity.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…On the contrary, the a value in different studies conducted in the same lakes was higher than the current study [19,27,29,33,37,42,44,45,47,48,57,58] . The b value calculated in this study higher than the b value of C. Gibelo studied in Danube River, Bafra Dam, İkizcetepeler Dam, Gelingüllü Dam, Seyitler Dam, Büyük Menderes basin, Beyşehir and Marmara Lake [52,51,58,48,27,47,44,45,57,33] . The length-weight relationship parameters can be affected by factors such as sampling period, nutritional status, heightweight distribution, reproductive period, age, and gonad maturity.…”
Section: Discussioncontrasting
confidence: 57%
“…The female-male ratio, lengthweight values and length-weight relationships determined in different studies with C. gibelio are summarized in Tables 2, 3 and 4, respectively. Eğirdir Lake 329/287 1:1.15 [30] Zegrzynski Reservoir, Vistula River (Poland) -1:0.21 [31] Eğirdir Lake 112/230 1:2.05 [19] Inland Waters of Estonia -1:0.67-0.85 [13] Ömerli Dam Lake 241/17 1:0.07 [32] İznik Lake 210/134 1:0.64 [32] Lake Pamvotis, Kalamas R., the Ionian Sea basin (Greece) -1:0.03 [14] Bafra Dam Lake 168/5 1:0.03 [33] ~ 68 ~ Beyşehir Lake 251/231 1:0.92 [34] Eğirdir Lake 823/894 1:1.09 [35] Dyje River, Morava River, Black Sea basin (Czech Rep.) -1:0.29 [36] Buldan Dam Lake 2312/13 1:0.01 [37] Topçam Dam Lake 170/2 1:0.01 [38] Lake Pamvotis (Greece) 1323/31 1:0.02 [39] Dyje River, Morava River, Black Sea basin (Czech Rep.) -1:0.26 [40] Uluabat Lake -1:0.52 [41] Uluabat Lake 419/153 1:0.37 [42] Aksu River Estuary 81/47 1:0.58 [43] İkizcetepeler Baraj Lake 374/106 1:0.28 [44] Gelingüllü Barajı 139/193 1:1.39 [45] Ladik Lake 140/10 1:0.07 [46] Seyitler Dam Lake 125/24 1:0.19 [47] Seyhan Dam Lake 142/18 1:0.13 [27] Seyhan Dam Lake 299/18 1:0.06 [48] Dyje River, Morava River, Black Sea basin (Czech Rep.) -1:0.31 [49] İznik Lake 2054/1060 1:0.51 [50] Beyşehir Lake 708/780 1:1.10 [51] Marmara Lake 809/249 1:0.31 [52] Siemianowka Reservoir, Narew R., Poland -1:0.32 [53] Ulugöl Plateau Pond 14/10 1:0.71 [54] Bafra Balık Lake 477/153 1:0.32 Present study…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LWRs of the invasive species found from the Gediz River`s different water resources changed respectively between b = 3.023 from Marmara Lake and b = 4.347 from Demirköprü Reservoir for C. gibelio; and b = 3.423 from Demirköprü Reservoir and b = 3.921 from Marmara Lake for A. boyeri (Güçlü, Küçük 2021). In another study, the b value was found to be b = 2.965 (for combined sexes) for C. gibelio species from Marmara Lake (Ilhan et al 2020). In the current study, the b value of C. gibelio was found to be b = 2.914 from Akgöl Lake.…”
Section: Lwrs Analysismentioning
confidence: 91%
“…The existence of C. gibelio in Turkish inland waters was first reported in Lake Gala in 1986 (Baran and Ongan, 1988). The rapid spread of invasive species in Turkish inland waters was reported in many studies which led to a negative impact on native species and local habitats (İnnal and Erk'akan, 2006;Tarkan et al, 2012b;İlhan et al, 2020). In a few studies, C. gibelio was previously reported in the Middle Black Sea Region (Yılmaz et al, 2012;Bostanci et al, 2016;Macun, 2018;Akbay, 2019).…”
Section: Introductionmentioning
confidence: 97%